Moving Beyond Task Efficiency: How Generative AI Challenges Teamwork - Mayer, Timo; Schwehn, Tim-Julian (ECIS 2025 Proceedings, 2025)
Organizations are increasingly introducing Generative Artificial Intelligence (GenAI) into teams based on the assumption that it enhances team performance. However, the specific role and impact of GenAI in team contexts remain underexplored. To address this gap, we conducted an exploratory case study in a large multinational industrial corporation. Using semi-structured interviews, observational data, and internal documents, we investigated how GenAI influences teamwork. Our preliminary findings reveal significant effects on team inputs, mediators, and perceived performance. Specifically, while GenAI improves, for instance, task efficiency, it also presents challenges such as hindered learning, communication breakdowns, and information overload, among other
Keywords: Generative Artificial Intelligence; Team-AI Collaboration; Team Performance